ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN OUTSOURCHING DI APARTEMEN “X” SURABAYA - Navandi, Dhony; Hwihanus, Hwihanus; Riyadi, Slamet (Universitas Of Surakarta, 2023)
This research aims to know influence of work motivation in improving the employees performan of Building Management Apartemen “X” on East Surabaya. This research applied descriptive qualitative research. The supervisor as head departement is important for the company because it has a role as a potential activator off all corporate activities. Companies that have qualified human resources can easily integrate corporate vision with corporate goals that have been set before.it can be conuluded that the high motivation in achieving a higher to interact or have a good relationship with others, and have a high motivation in reaching a power or have influence on others.